Pengaruh Penggunaan E-Wallet, Literasi Keuangan dan Kemudahan Bertransaksi Terhadap Perilaku Konsumtif Pelaku UMKM di Kabupaten Bondowoso - Karomah, Lailatul; Martini G, Ni Nyoman Putu; Wijayantini, Bayu (ICON Publisher, 2025)
Rapid development and progress have brought significant changes in various aspects of life, including in people's consumption patterns. Technological advances and digitalization that occurred in the industrial era 4.0 have made it easier for individuals to access various products and services online. This study aims to analyze the influence of e-wallet use, financial literacy, and ease of transactions on the consumptive behavior of MSMEs in Bondowoso Regency. The object of this study was MSMEs in Bondowoso Regency. This study used quantitative methods and a sample size of 100 respondents. The sampling technique used proportional sampling and purposive sampling. The data collection technique used a questionnaire distributed to respondents. Data analysis used in this study was instrument testing, classical assumption testing, multiple linear regression analysis, t-hypothesis testing (partial), and coefficient of determination (R2) testing with the help of the SPSS (Statistical Package for Social Science) program. The results of the study indicate that e-wallet use and ease of transactions do not significantly influence MSMEs' consumer behavior, while financial literacy does. Based on the coefficient of determination test, the contribution obtained was 28%.